Electromyographic analysis of forearm muscles in professional and amateur golfers - Farber, A. J.; Smith, J. S.; Kvitne, R. S.; Mohr, K. J.; Shin, S. S. (The American Journal of Sports Medicine, 2009)
Background No fine-wire electromyography studies have been performed to compare the activity of forearm muscles in professional golfers versus amateur golfers.